Physical Growth and Body Adiposity Curves in Students of the Maule Region (Chile) - Gomez-Campos, Rossana; Arruda, Miguel; Andruske, Cynthia Lee; Leite-Portella, Daniel; Pacheco-Carrillo, Jaime; Urral-Albornoz, Camilo; Sulla-Torres, Jose; Luarte-Rocha, Cristian; Cossio-Bolaños, Marco Antonio (Frontiers in Pediatrics, 2019)
Objectives: Physical growth and body adiposity patterns provide relevant information to infer the nutritional and health status of students. Our objectives were (a) to compare the variables of body adiposity and physical growth of Chilean children and adolescents with data from the CDC-2012 and international studies, and (b) to develop regional reference curves to evaluate growth and body adiposity. Methods: 8,261 children and adolescents were studied. We evaluated the weight, height, and waist circumference (WC). The Body Mass Index (BMI) was calculated. Their physical growth and body adiposity were compared with the CDC-2012 references as well as with other international references. Percentile curves for weight, height, BMI, and WC were constructed with the LMS method. Results: The Chilean students showed reduced weight and height during adolescence when compared with the CDC-2012 reference. During early ages, the BMI for the Chilean sample was lower while at advanced ages, the WC values were greater in comparison to the CDC-2012 reference. Graphic comparisons with international studies indicated that Chilean students weighed more at all ages. However, height was slightly greater until age 14 for males and age 11 for females. Body adiposity (BMI and WC) for the Chilean students was slightly higher at early ages while at later ages, adiposity values were relatively similar for both sexes. Conclusions: Discrepancies were observed between the physical growth and body adiposity trajectories and the American CDC-2012 references and the international studies. The proposed percentiles for weight, height, BMI, and WC for each age and sex may be useful for health sciences professionals and researchers.